Incorporation of Kojic Acid-Azo Dyes on TiO2 Thin Films for Dye Sensitized Solar Cells Applications - Zie, Carolynne Wei Sie; Zainab, Ngaini (Hindawi Publishing Corporation, 2017)
Sensitization of heavy metal free organic dyes onto TiO2 thin films has gainedmuch attention in dye sensitized solar cells (DSSCs). A series of new kojic acid based organic dyes KA– were synthesized via nucleophilic substitution of azobenzene bearing different vinyl chains A– with kojyl chloride . Azo dyes KA– were characterized for photophysical properties employing absorption spectrometry and photovoltaic characteristic in TiO2 thin film. The presence of vinyl chain in A– improved the photovoltaic performance from 0.20 to 0.60%. The introduction of kojic acid obtained from sago waste further increases the efficiency to 0.82–1.54%. Based on photovoltaic performance, KA achieved the highest solar to electrical energy conversion efficiency (